1989
DOI: 10.1021/bi00444a035
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of troponin I and its inhibitory fragment (residues 104-115) with troponin C and calmodulin

Abstract: Fluorescent probes have been used to study the interaction of troponin I and its inhibitory peptide TnIp with troponin C, calmodulin, and the proteolytic fragments of calmodulin. The probes used included the noncovalently bound ligand TNS and the covalently attached labels dansyl and AEDANS. The fluorescence intensity of TNS bound to troponin C, calmodulin, or the calmodulin fragments was greatly enhanced by the presence of TnIp. This effect was used to estimate the corresponding binding constants. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…TnIp has been shown to interact with the C-terminal domain of TnC (Leavis et al, 1978;Weeks & Perry, 1978;Chong & Hodges, 1981;Grabarek et al, 1981;Wang & Cheung, 1984;Tao et al, 1986Tao et al, , 1989Leszyk et al, 1987;Lan et al, 1989). Here, we present a 'H NMR comparison of TnIp binding to s-TnC and TnIp binding to an SCIII/SCIV heterodimer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TnIp has been shown to interact with the C-terminal domain of TnC (Leavis et al, 1978;Weeks & Perry, 1978;Chong & Hodges, 1981;Grabarek et al, 1981;Wang & Cheung, 1984;Tao et al, 1986Tao et al, , 1989Leszyk et al, 1987;Lan et al, 1989). Here, we present a 'H NMR comparison of TnIp binding to s-TnC and TnIp binding to an SCIII/SCIV heterodimer.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies indicate that the TnI peptide interacts with the C-terminal domain of TnC (Weeks & Perry, 1978;Grabarek et al, 1981;Cachia et al, 1983;Drabikowski et al, 1985;Leszyk et al, 1987Leszyk et al, , 1988Lan et al, 1989). In the present study we use 'H NMR spectroscopy to compare the binding of TnIp to the synthetic noncovalent heterodimer comprised of site 111 and site IV peptides with the binding of TnIp to calcium-saturated s-TnC.…”
Section: ;mentioning
confidence: 99%
“…A large number of reports have studied the molecular interaction between TnI and TnC (Horwitz et al, 1979;Lan et al, 1989;Leszyk et al, 1990;Miki, 1990;Wang et al, 1990;Farah et al, 1994;Guo et al, 1994;Kobayashi et al, 1994). In vitro experiments with purified proteins and also with synthetic peptides have established the interactions among several muscle proteins and the participating domains.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies have also concluded that TnIp interacts primarily with regions in the C-terminal domain (Lan et al, 1989;Wang et al, 1990;Ngai & Hodges, 1992;Swenson & Frederickson, 1992;Ngai et al, 1994). Fluorescent probes reveal that, although intact sTnI is bound to both the N-and C-terminal domains of sTnC, the inhibitory fragments of sTnI (96-1 16 and 104-1 15) interact mainly with the C-terminal domain connecting strand of sTnC (Lan et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent probes reveal that, although intact sTnI is bound to both the N-and C-terminal domains of sTnC, the inhibitory fragments of sTnI (96-1 16 and 104-1 15) interact mainly with the C-terminal domain connecting strand of sTnC (Lan et al, 1989). This is in excellent agreement with our observation that Met 120 and Met 157, both at the outer edge of the hydrophobic pocket in the C-terminal domain of cTnC, are protected by the binding of cTnI peptide.…”
Section: Discussionmentioning
confidence: 99%